Cerebral Psychophysiology of Depression: Preliminary Results - Lolas, Fernando; De la Parra, Guillermo (Investigación Clínica, 2009)
Some features of psychophysiological research are discussed on the basis of preliminary data derived from vertex slow potentials (contingent negative variation, CNV) recorded during reaction-time paradigms in normal subjects and depressive patients. Peak amplitude and area failed to discriminate between ";neurotic"; and ";endogenous"; depressives defined according to clinical criteria, although a trend toward higher amplitudes was evidenced in the endogenous group. The need for a more accurate description at the behavioural level is emphasized, along with some suggestions for further research resting upon a multivariate approach to psychiatric electrophysiology.